Chad : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In October 2006, the Chadian government prepared a second National Poverty Reduction Strategy (NPRS2). NPRS2 analyzed poverty in Chad, reviewed the results of the first NPRS and progress toward the Millennium Development Goals (MDGs), defined the strategic pillars of the second strategy, examined two key scenarios for poverty reduction and growth, and described the institutional framework for implementation of the strategy. The government considers NPRS2 as the main instrument for achieving the MDGs in Chad, and therefore the preferred framework for socioeconomic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet